PO214 Neuropsychological sequelae of viral meningitis. (1st December 2017) - Adan, Guleed; Griffiths, Mike; Bonnett, Laura; Miller, Alastair; Geretti, Anna Maria; Michael, Benedict; Beeching, Nick; McKee, David; McGill, Fiona; Solomon, Tom
Abstract : Background: Survivors of bacterial meningitis are known to suffer neuropsychological deficits after their acute illness. Previous studies have suggested that viral meningitis may also cause cognitive problems. Primary and Objective: We aimed to determine what the neuropsychological problems encountered by adults with viral meningitis were compared to healthy patients without meningitis and how long their problems lasted. Methods: Patients with viral meningitis and healthy controls completed the 'Aldenkamp and Baker Neuropsychological Assessment Schedule (ABNAS)', a 24 item self-administered questionnaire. Patients completed the ABNAS at 4 time points – 6, 12, 24 and 48 weeks post acute illness. Higher ABNAS scores correspond to greater levels of neuropsychological dysfunction, with a worst score possible of 72. Results: Healthy controls (n=224) had a mean total ABNAS score of 7. Comparatively, the patients with viral meningitis had significantly worse scores at all 4 time points. At 6 weeks scoring 22 (p<0.001) (n=73), at 12 Weeks 19.5 (p<0.001) (n=102), at 24 weeks 13.5 (p 0.002) (n=86) and at 48 weeks 16.5 (p<0.001) (n=76). Conclusions: Patients with viral meningitis have significantly worse neuropsychological deficits compared to healthy controls. The deficits showed some improvement initially but failed to improve significantly beyond 24 weeks.